The "iPhone effect": The impact of dual technological disruptions on electrification. Issue 2 (June 2020) - Fuentes, Rolando; Hunt, Lester C.; Lopez-Ruiz, Hector; Manzano, Baltasar
Meeting climate change goals requires both the decarbonization of the electricity sector and the electrification of much of the rest of the economy. However, the electricity sector is navigating major disruptions that are changing the regulatory and business landscape. This article focuses on the question of whether these changes would help or hinder electrification, taking transportation as an example. Like the electricity sector, transportation is undergoing a deep transformation. We suggest that businesses in both sectors will at some point offer aggregated services, repackaged as subscriptions, and traded on digital platforms. We also argue that data created by these activities would be so valuable that this could be reason alone to move toward this model. This could create synergies between companies that could eventually lead to a rebound effect of electrification, with more vehicle miles traveled and more electricity consumption than before.